Lysinuric protein intolerance with novel mutations in solute carrier family 7A member 7 in a Chinese family - Yilin Pang; Feng Huo; Xiao Liu; Yimu Fan; Zhezhe Zhang; Jie Wu; Quan Wang (Wiley, 2024)
ABSTRACT Introduction Lysinuric protein intolerance (LPI) is a rare genetic disorder caused by mutations in the solute carrier family 7A member 7 (SLC7A7) gene. Case presentation We presented two siblings with LPI, carrying novel mutations of c.776delT (p.L259Rfs*18) and c.155G>T (p.G52V) in SLC7A7. The younger sibling, preferring protein‐rich foods, showed severe symptoms, including alveolar proteinosis, macrophage activation syndrome, severe diarrhea, and disturbance of consciousness with involuntary movements. In contrast, the elder sibling only had mild symptoms, likely due to aversion to protein‐rich food since toddler age. Conclusion LPI is a congenital genetic metabolic disease with multi‐system involvement. Initiating appropriate protein‐restricted diet therapy as soon as possible could help prevent the progression of LPI.